Effect of cup medialization on primary stability of press-fit acetabular cups. (December 2020) - Morosato, Federico; Cristofolini, Luca; Castagnini, Francesco; Traina, Francesco
Abstract: Background: Appropriate restoration of the native centre of rotation is of paramount importance in total hip arthroplasty. Reconstruction of the centre of rotation depends on reaming technique: conventional approaches require more cup medialization than anatomical preparations. To date, the influence of cup medialization on socket stability in cementless implants is still unknown. Methods: Ten cadaveric hemipelvises were sequentially reamed using anatomical technique (only subchondral bone removal with restoration of the native centre of rotation) and conventional preparation (reaming to the lamina and medializing the cup). A biomechanical test was performed on the reconstructions. Implant motions were measured with digital image correlation while a cyclic load of increasing magnitude was applied. Findings: No significant difference was measured between the two implantation techniques in terms of permanent cup migrations. The only significant difference was found for the cup inducible rotations, where the conventional technique was associated with larger rotations. Interpretation: Conventional reaming and cup medialization do not improve initial cup stability. Beyond the recently questioned concerns about medialization and hip biomechanics, this is another issue to bear in mind when reaming the acetabulum. Highlights: We assessed the effects of medialization of press-fit hip cups on implant stability. Cadaveric pelvises were sequentially reamed to place the cup at increasing depths. We used digital image correlation to measure implant displacements under cyclic load. While permanent migration was unaffected, cup medialization increased inducible rotation. Deeper reaming and cup medialization do not improve initial cup stability.